Proto-oncogene Activity of Melanoma Antigen-A11 (MAGE-A11) Regulates Retinoblastoma-related p107 and E2F1 Proteins - Su, Shifeng (American Society for Biochemistry and Molecular Biology, 2013)
Melanoma antigen-A11 (MAGE-A11) is a low-abundance, primate-specific steroid receptor coregulator in normal tissues of the human reproductive tract that is expressed at higher levels in prostate cancer. Increased expression of MAGE-A11 enhances androgen receptor transcriptional activity and promotes prostate cancer cell growth. Further investigation into the mechanisms of MAGE-A11 function in prostate cancer demonstrated interactions with the retinoblastoma-related protein p107 and Rb tumor suppressor but no interaction with p130 of the Rb family. MAGE-A11 interaction with p107 was associated with transcriptional repression in cells with low MAGE-A11 and transcriptional activation in cells with higher MAGE-A11. Selective interaction of MAGE-A11 with retinoblastoma family members suggested the regulation of E2F transcription factors. MAGE-A11 stabilized p107 by inhibition of ubiquitination and linked p107 to hypophosphorylated E2F1 in association with the stabilization and activation of E2F1. The androgen receptor and MAGE-A11 modulated endogenous expression of the E2F1-regulated cyclin-dependent kinase inhibitor p27(Kip1). The ability of MAGE-A11 to increase E2F1 transcriptional activity was similar to the activity of adenovirus early oncoprotein E1A and depended on MAGE-A11 interactions with p107 and p300. The immunoreactivity of p107 and MAGE-A11 was greater in advanced prostate cancer than in benign prostate, and knockdown with small inhibitory RNA showed that p107 is a transcriptional activator in prostate cancer cells. These results suggest that MAGE-A11 is a proto-oncogene whose increased expression in prostate cancer reverses retinoblastoma-related protein p107 from a transcriptional repressor to a transcriptional activator of the androgen receptor and E2F1.